URGENSI PEMBERIAN HAK ATAS TANAH KEPADA PENANAM MODAL DALAM PERSPEKTIF TEORI HUKUM ALAM - Fries Melia Salviana (Perspektif, 2020)
Kajian penulisan ini adalah urgensi Pemberian Hak Atas Tanah kepada Penanam Modal berdasarkan perspektif Teori Hukum Alam. Landasan pengaturannya ada pada Pasal 33 UUD 1945 bahwa pemanfaatan tanah dapat dilakukan jika digunakan untuk kesejahteraan masyarakat. Pengaturan mengenai pemberian hak atas tanah pada penanam modal asing dalam Hak Guna Bangunan, Hak Guna Usaha, dan Hak Pakai sebagaimana diatur dalam Pasal 2 UUPA. Pengaturan tersebut dalam rangka pemberian fasilitas dalam bentuk insentif berdasarkan kriteria berdasarkan Pasal 18 UU Penanaman Modal. Pemberian hak atas tanah kepada penanam modal asing telah sesuai dengan hukum alam yang mewajibkan adanya kebaikan umum guna mencapai keadilan protektif dengan adanya hak menguasai yang memberikan kewenangan untuk menentukan penataan penggunaan tanah dengan hak rakyat. Serta penanaman modal yang merupakan peningkatan modal untuk pembangunan ekonomi berkelanjutan dan peningkatan ekonomi, alih teknologi, peningkatan lapangan kerja dan pengembangan ekonomi kerakyatan. Sehingga dengan demikian berdasarkan dengan kebaikan negara, maka tentunya aturan yang telah dibuat terkait dengan pemberian hak atas tanah tersebut di atas tentunya adalah harus mensyaratkan kepedulian atas kebaikan bersama, yaitu peningkatan kesejahteraan di Indonesia.The study in this paper is the urgency of Granting Land Rights to Investors based on the perspective of Natural Law Theory. The basis for regulating land rights is contained in Article 33 of the 1945 that use of land can used for welfare of the community. Article 2 of the UUPA also stipulates that granting land rights to foreign investors can only be granted of Building Use Rights, Business Use Rights, and Use Rights. The granting of land rights for foreign investors which is a facility in the form of incentives is regulated with a benchmark in the form of criteria contained in Article 18 Investment Law. Granting of land rights to foreign investors is in accordance with natural law which requires public good protective justice with existence of control rights which give authority to determine the arrangement of land use by taking into account people’s rights to land. As well as foreign investment which is an increase in capital for sustainable economic development and economic improvement, technology transfer, increased employment and development of a people’s economy. The limitations and requirements provided are also a form of protection for the community so that protective justice with a standard of general good is achieved. The recommendation given is the addition of regulations regarding the granting of land rights to foreign investors particular and use of powers related to the right to control by the government by means of restrictions in the form of requirements for granting land rights. Thus, based on the goodness of the state, of course the rules that have been made regarding the granting of rights to the land mentioned above, of course, must require concern for the common good, namely increasing welfare in Indonesia.